Verifying Experimental Wet Bulb Globe Temperature Hindcasts Across the United States - Yoonjung Ahn; Christopher K. Uejio; Jared Rennie; Lisa Schmit (GeoHealth, 2022)
Abstract Hot and humid heat exposures challenge the health of outdoor workers engaged in occupations such as construction, agriculture, first response, manufacturing, military, or resource extraction. Therefore, government institutes developed guidelines to prevent heat‐related illnesses and death during high heat exposures. The guidelines use Wet Bulb Globe Temperature (WBGT), which integrates temperature, humidity, solar radiation, and wind speed. However, occupational heat exposure guidelines cannot be readily applied to outdoor work places due to limited WBGT validation studies. In recent years, institutions have started providing experimental WBGT forecasts. These experimental products are continually being refined and have been minimally validated with ground‐based observations. This study evaluated a modified WBGT hindcast using the historical National Digital Forecast Database and the European Centre for Medium‐Range Weather Forecasts Reanalysis v5. We verified the hindcasts with hourly WBGT estimated from ground‐based weather observations. After controlling for geographic attributes and temporal trends, the average difference between the hindcast and in situ data varied from −0.64°C to 1.46°C for different Köppen‐Geiger climate regions, and the average differences are reliable for decision making. However, the results showed statistically significant variances according to geographical features such as aspect, coastal proximity, land use, topographic position index, and Köppen‐Geiger climate categories. The largest absolute difference was observed in the arid desert climates (1.46: 95% CI: 1.45, 1.47), including some parts of Nevada, Arizona, Colorado, and New Mexico. This research investigates geographic factors associated with systematic WBGT differences and points toward ways future forecasts may be statistically adjusted to improve accuracy.